De l’activisme à la négociation urbaine. Dynamiques d’engagement politique et environnemental à la Floating University de Berlin - Antoine Apruzzese (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
The Floating University project, developed in 2018 by the Berlin-based collective Raumlabor, is a complex and hybrid architectural project, thought of as a laboratory of collective experimentation on the relationship between our urban societies and the environment. The project came after ten years of temporary urban interventions on the site of the former Tempelhof airport. Raumlabor’s projects aimed to set up the cultural conditions for the development of a local community that shares common social and environmental values and is capable of acting upon its own condition of inhabiting the city. The architectural and programmatic evolution of the site shows different dynamics of political engagement, both from the collective and the association that have taken over and kept the project afloat following Raumlabor.